COVID-19: dealing with disposables - Ismawi, Hidayatul Radziah; Ab. Rashid, Iqbalmunauwir; Suhaimi, Mohamad Suhaizi; Abdul Rashid, Amirah; Dzaharudin, Fatimah; Sidek, Dinsuhaimi; Mohd Ishak, Siti Haida; Idris, Rostam Iffendi (Malaysian Integrated Medical Professionals Association, 2021)
The Ta'ruf Intellectual DIscourse (TIDE) is a course for newly appointed academic staff for permanent basis and contract basis staff. This course is one of the compulsory courses for new staff. In this course, participants will know the role and functions of various Kulliyyahs, Centres, Departments, and Institutes in the International Islamic University Malaysia (IIUM). In 2021, for the first time, TIDE 52 was conducted online via both asynchronous & synchronous sessions. Participants were split into small groups to complete activities based on assigned themes. The final group activity was to solve a case scenario by incorporating aspects of the Insan Sejahtera Framework. This e-book is based on Group 8's efforts & ideas and embraces the concept of open access of knowledge and sustainability.